The Cotton Sector of Côte d'Ivoire - Gergely, Nicolas (World Bank, Washington, DC, 2017)
This report is the final product of a country case study prepared in the framework of the comparative analysis of organization and performance of cotton sectors in Sub-Saharan Africa, a study published by the World Bank in 2008. The objective of the overall study was to carry out a comparative analysis of the links between sector structure and observed performance outcomes on a sample of nine of the major cotton exporting countries of Sub-Saharan Africa, and draw lessons from each country's experience that can provide useful guidance to policy-makers, industry stakeholders, and interested donors agencies in the design of future cotton sector reform programs. This paper describes and reviews the situation of the cotton sector of Cote d'Ivoire, as well as the reforms that the sector has undergone since the mid-1990s.